Diagnosis of Cryptococcosis and Prevention of Cryptococcal Meningitis Using a Novel Point-of-Care Lateral Flow Assay - Ashar Dhana (Case Reports in Medicine)
Despite access to antiretroviral therapy, mortality from cryptococcal meningitis (CM) is high among persons with advanced HIV infection in sub-Saharan Africa. Cryptococcal antigen (CrAg) is present several weeks to months before the onset of symptoms of meningitis and can be screened to prevent life threatening meningitis. Recently, the World Health Organisation recommended that a new rapid CrAg lateral flow ‘‘dipstick’’ assay (LFA) is to be used to screen HIV-infected persons with CD4 counts of less than 100 cells/µL. In this paper, we describe two cases of cryptococcosis with differing outcomes. In the first case, the new CrAg LFA was used as part of a screen and preemptive treatment strategy to prevent CM. In the second case, our patient had no access to the CrAg LFA and subsequently developed life threatening meningitis. To the best of our knowledge, this is the first case report of cryptococcosis diagnosed using this novel assay.